(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article is dedicated to the work of Professor Abdurauf Fitrat, a great representative of the twentieth century, and "Family or Family Management Procedures." The main issue was the moral upbringing of the child in the family, and an attempt was made to compare it with the views of Eastern thinkers who lived and worked before him. Fitrat divides the upbringing of a child into three types and explains how it can lead to unpleasant situations if not enough attention is paid to moral upbringing.